2021
DOI: 10.3389/fpsyg.2021.724463
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Mechanism of Knowledge-Based Professionals’ Core Value Identity on Creativity From the Perspective of the Knowledge Economy

Abstract: In the era of the knowledge economy, tacit knowledge transfer is a key strategy for developing personal creativity, but it also is affected by core value agreement. Knowledge-based professionals have innate sensitivity with core value agreement. In the knowledge capital development system, tacit knowledge transfer is a key strategy to be discovered. This research investigates the core value identity mechanism of knowledge professionals from the perspective of the knowledge economy. The results revealed the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Through an in-depth theoretical examination of how tacit knowledge encompassing both knowledge donating and collecting is shared in these SMEs, this study gains insights into its direct contribution to improving innovation capability at both individual and organizational levels. According to Işık et al, (2021); Von Krogh, (1998); Zhou et al, (2021) and Tri (2018) tacit knowledge sharing is a critical mechanism for innovation, enabling employees to absorb and utilize uncodified experiential knowledge from their peers. This exchange goes beyond the mere acquisition of explicit information and promotes a deeper and intrinsic form of learning.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through an in-depth theoretical examination of how tacit knowledge encompassing both knowledge donating and collecting is shared in these SMEs, this study gains insights into its direct contribution to improving innovation capability at both individual and organizational levels. According to Işık et al, (2021); Von Krogh, (1998); Zhou et al, (2021) and Tri (2018) tacit knowledge sharing is a critical mechanism for innovation, enabling employees to absorb and utilize uncodified experiential knowledge from their peers. This exchange goes beyond the mere acquisition of explicit information and promotes a deeper and intrinsic form of learning.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The creation and dissemination of tacit knowledge results from the process of socialization, the sharing of experiences, and the interactive skills of individuals to communicate with their colleagues (Von Krogh, 1998). Effective knowledge creation and sharing through internal and external stakeholder interactions enhances an individual's critical thinking and creativity by acquiring valuable tacit knowledge (Zhou et al, 2021). Furthermore, Tri (2018) emphasizes sharing tacit knowledge allows individuals to learn from others' skills, perspectives, and experiences with successes and failures, including their ideals, principles, and feelings which are not readily accessible through formal training or explicit knowledge sources.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“… Sarwoko and Nurfarida (2021) mentioned that internal locus of control, motivation to achieve goals, moderate level of risk-taking propensity, creativity, capacity to tolerate stress, along with higher levels of self-efficacy are key dispositions required by an entrepreneur ( Kusumawijaya and Astuti, 2021 ). In a knowledge-based economy creativity and innovation have been highlighted as significant aspects of personality traits and have been termed as the psychological intelligence element of human beings and knowledge is regarded as the considered as the critical element to develop this personality trait ( Zhou et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Entrepreneurial education was found to develop entrepreneurial personality traits in college students and thus results more entrepreneurial intention among these students, ( Zhou et al, 2021 ). Moreover, Zhou et al (2021) revealed that the knowledge is the professional base for developing the entrepreneurial personality in individuals that motivate them towards start ups.…”
Section: Research Framework and Hypotheses Developmentmentioning
confidence: 99%
“…Adaptation of a strategy is a process of “matching” or “matching the organizational resources” with the opportunities of the environment ( Ruobing et al, 2022 ). At present, there is a lack of relevant reasons in the academic circle, and only the difference in creativity characteristics during entrepreneurship is regarded as the influencing factor ( Jiatong et al, 2021b ; Xie et al, 2021 ), but the creativity characteristics are more the external expression of technical ability and transfer of knowledge ( Zhou et al, 2021 ), which do not reflect the personal characteristics that affect the major decision-making and management of enterprises. Therefore, the key research questions of this study are framed as (1) What are the cognitive and affective factors that affect strategic decision-making abilities?…”
Section: Introductionmentioning
confidence: 99%